The dynamics of the role of women workers abroad to improve the family economy: The perspective of Islamic economics - Audia, Nanda; Ningsih, Nur Wahyu; Kurniawan, Arifa; Pramasha, Raizky Rienaldy (Nur Science Institute, 2023)
Family economics is a branch of microeconomics that focuses on managing resources to ensure an individual's or small-scale family's survival. It examines how a family's economic status influences their consumption level. It is assumed that as the economic level of a family improves, their expenditures also increase. As household income increases, families tend to purchase more goods and may adopt a more materialistic lifestyle, seeking higher-quality products. This study aims to explore the economic conditions of families with female overseas laborers (TKWs) and understand how their participation in work abroad affects their family's income. The qualitative research method employed in this study utilizes a phenomenological approach, which involves structured interviews, participant observation, and documentation. Primary and secondary data sources are used to collect data. The research findings suggest that the involvement of TKWs has been beneficial in enhancing the family economy. The condition is evident from comparing income levels before and after individuals become TKWs. Women's primary motivation for overseas work is to boost their income.